2009
DOI: 10.1577/m06-032.1
|View full text |Cite
|
Sign up to set email alerts
|

Fishers' Reasons for Poaching Abalone (Haliotidae): A Study in the Baja California Peninsula, Mexico

Abstract: Although Mexico has a well-established legal framework regulating fisheries for the green abalone Haliotis fulgens and pink abalone H. corrugata, there is empirical evidence about a sizeable abalone black market and substantial sectors of fishing communities dedicated to poaching. An investigation was conducted about abalone poaching in a bay located off the Baja California Peninsula, Mexico. The main objective was to determine how poaching is perceived by abalone fishermen, particularly the attitudes of legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
0
9
0
1
Order By: Relevance
“…Permit holders and independent fishermen are further provided incentive to shelter and/or underreport their catches by the prices that globally demanded seafood can fetch on the black market (Ibarra and Ramírez Soberón 2002). One study on the Pacific coast of Baja California (Reyes et al 2009) concluded that abalone received and legitimized through official channels would garner fishermen only half the value that could be obtained when the product was sold on the black market. In the Gulf of California, market intermediaries with connections to the black market may channel international demand for high value species like sea cucumber (Ibarra and Ramírez Soberón 2002), turtle (Mancini et.…”
Section: Social-ecological Interactionsmentioning
confidence: 99%
“…Permit holders and independent fishermen are further provided incentive to shelter and/or underreport their catches by the prices that globally demanded seafood can fetch on the black market (Ibarra and Ramírez Soberón 2002). One study on the Pacific coast of Baja California (Reyes et al 2009) concluded that abalone received and legitimized through official channels would garner fishermen only half the value that could be obtained when the product was sold on the black market. In the Gulf of California, market intermediaries with connections to the black market may channel international demand for high value species like sea cucumber (Ibarra and Ramírez Soberón 2002), turtle (Mancini et.…”
Section: Social-ecological Interactionsmentioning
confidence: 99%
“…Accordingly, in comanagement regimes, poaching control should combine coercive measures with organizational strengthening and participatory monitoring, which promote compliance (Ballesteros et al, 2021). Therefore, understanding human perceptions of IUU and their motivations is a starting point for proposing comprehensive control strategies (Reyes et al, 2009;Kahler and Gore, 2015;Ballesteros and Rodríguez-Rodríguez, 2018a,b;Epanda et al, 2019). This poses an important challenge for Chile, in which the characterization and quantification of attitudes and motivations for IUU is necessary to make progress in in the sustainable management of fisheries (Hampshire et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The probability of success in abalone poaching is a factor with significant influence on fishers' perceptions of poaching. The low risk of being caught by authorities and the harvest volume per working day are elements that make abalone poaching a highly appealing activity (Bórquez-Reyes et al 2009). High market value and vulnerability of abalone stocks are strong incentives that induce illegal fishing.…”
Section: Discussionmentioning
confidence: 99%
“…The methods proved to be adequate for estimating the illegal catch of coastal fisheries at a local level, and could be used as a bottom-up approach for estimating illegal catch. jornada laboral son elementos que convierten la pesca ilegal de abulón en una actividad muy atractiva (Bórquez-Reyes et al 2009). El alto valor en el mercado y la vulnerabilidad de las poblaciones de abulón son fuertes incentivos que promueven la pesca ilegal.…”
Section: Discussionunclassified